Entre deuses e Deus : estratégias e táticas na implantação do presbiterianismo no estado de Mato Grosso-primeira metade do século XX - Arruda, Emerson de (2018)
This research has as a general goal, to analyze the strategies and tactics used in the planting of Presbyterianism in the state of Mato Grosso during the first half of the twentieth century, assuming as point of analyses the proselytism effected by the North-American missionaries of the Presbyterian Church of Brazil For the effectuation of this thesis, many internal documents of the Presbyterian Church of Brazil were used, such as: Books of minutes of Presbyterian churches and the foreign missions committee; Field reports and journals of missionaries; and, the bibliographical construction of many dissertations and thesis which analyze the historical, political and religious scenery of Mato Grosso during this time period. The theoretical-methodological perspective adopted in this research, which also gives structure to the analysis of data, is one which is inherent to the qualitativeinterpretative approach, surrounding itself in the theoretical matrix of cultural history, interconnected to the field: History of Religion. In this investigative process, two categories from the French historian Michel Certeau: “Strategy” and “Tactics” were applied. Which in a certain way, enabled the comprehension of the planting process of Presbyterianism and the production of senses by this new religion in Mato Grosso, interfering in the cultural, religious and educational spheres. The data analyzed, until the present moment, which still do not have a conclusive character, point toward the fact that this institution, in its application of its proselytism, utilized education (through the building of technical schools and the moral formation from confessional schools), the communication (via a speech of progress in homily and doctrinal debates in newspapers) , catechizing (by means of indigenous evangelism) and political relations (building a dialogue with the fields and sectors which were seeking a new Mato Grosso), as strategies for the effectuation of its evangelizing actions. Thus, it is possible to ratify some Weberian concepts regarding the identity of Protestantism, but at the same time, realize that, in spite of a rational structure through normative and bureaucratic moral codes, the belief of a missionary responsibility, involving the transformation of individuals and of the world in its diverse sectors is interposed with the significant elements in the construction of a missionary identity in the Presbyterian Church in Mato Grosso. Thiis was financed in party by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance 001.